Kenakalan Remaja di Era Digitalisasi - Cinta Radila Putri; Ika Febriani; Jihan Khairunnisa; Arif Rusman; Adinda Fitria Chinthani; Hermalia Hermalia; Abraham Paskanda Situmorang; Azzahra Balqis Luqyana; Annisa Annisa; Dina Fitriyah (Lembaga Pengembangan Kinerja Dosen, 2025)
Adolescence is a very important transitional phase marked by significant physical, psychological, and social changes. These changes are prone to delinquent behavior, especially in today's digital age. Adolescent delinquency is not only in the form of conventional behaviors such as truancy and gang fights as before, but also in digital forms such as cyberbullying, gadget addiction, and social media abuse. This research and community service project aims to understand the definition, causes, impacts, and prevention strategies for juvenile delinquency in the digital age through outreach activities conducted by students participating in the Raja Ali Haji Maritime University's Community Service Program (KKN) at MTs Teluk Sasah. The outreach method involved presenting material and interactive discussions with students. The results of this activity showed an increase in students' understanding and awareness of juvenile delinquency and the need for the family's role in guiding them. The factors that drive juvenile delinquency can be categorized into internal factors (from within the self) and external factors (from the environment). These factors have impacts that include a decline in academic achievement, mental health disorders, and weakened social interaction. These activities have implications for the formation of collective awareness to protect adolescents from the negative influences of the digital age, while optimizing the potential of technology as a means of positive self-development.